PENGEMBANGAN SILABUS BAHASA INGGRIS KEBIDANAN DI UNIPDU SESUAI DENGAN LEVEL 5 KKNI (SEBUAH ANALISIS KEBUTUHAN) - Fitriana, Irta (Educate, 2015)
This research is based on the fact that the syllabus for learning English at D-3 Midwifery Unipdu Jombang was not appropriate with the needs of the profession of a midwife. The results showed that the syllabus‟ content of English required by the graduate of D3 midwifery Unipdu is as follows: General expressions: 1) common phrases to start and end a conversation with a client. 2) The introductory phrases. 3) Therapeutic greetings. 4) Numbers. 5) Time expressions. 6) Phrases to praise. 7) Phrases to calm someone. Grammar: 1) Yes / No questions / Wh questions. 2) Imperative sentences. Vocabulary: 1) Vocabulary about teens‟ physical changes. 2) Vocabulary on adolescent mental changes. 3) Vocabulary of the human‟s reproductive system. 4) Vocabulary related to pregnancy. 5) Vocabulary related to patient's vital signs. 6) Vocabulary of human‟s reproductive system. 7) Vocabulary related to childbirth. 8) Vocabulary related to signs of labor. 9) Vocabulary of stages of labor. 10) Vocabulary of after birth. 11) Vocabulary of contraception. 12) Vocabulary of newborn care. 13) Vocabulary of infant feeding. 14) Vocabulary of reproductive disorders in women Keywords: Syllabus, KKNI level 5, Needs Analysis